2021
DOI: 10.1371/journal.pone.0249247
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of COVID-19 infection in a rural district of South India: A population-based seroepidemiological study

Abstract: Objectives We aimed to estimate the seroprevalence of COVID-19 in a rural district of South India, six months after the index case. Methodology We conducted a cross-sectional study of 509 adults aged more than 18 years. From all the four subdistricts, two grampanchayats (administrative cluster of 5–8 villages) were randomly selected followed by one village through convenience. The participants were invited for the study to the community-based study kiosk set up in all the eight villages through village healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
63
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(74 citation statements)
references
References 13 publications
7
63
4
Order By: Relevance
“…It is crucial to recognize an infected person at an early stage to cut the transmission of COVID-19, although in reality they do not often require medication attention or contribute to rapid spread of the infection. But it is not sufficient to rely only on confirmed cases of COVID-19 cases detected by polymerase chain reaction (PCR) for control measures, as these tests often rule out asymptomatic and pre-symptomatic cases [ 6 ]. In order to overcome this challenge, A quantitative, population-based sero-epidemiological survey can better determine the entity of the population exposed to SARS-CoV-2 by revealing the proportion of the population with antibodies against the virus, to generate data on immunity status of population and to implement containment measures accordingly.…”
Section: Introductionmentioning
confidence: 99%
“…It is crucial to recognize an infected person at an early stage to cut the transmission of COVID-19, although in reality they do not often require medication attention or contribute to rapid spread of the infection. But it is not sufficient to rely only on confirmed cases of COVID-19 cases detected by polymerase chain reaction (PCR) for control measures, as these tests often rule out asymptomatic and pre-symptomatic cases [ 6 ]. In order to overcome this challenge, A quantitative, population-based sero-epidemiological survey can better determine the entity of the population exposed to SARS-CoV-2 by revealing the proportion of the population with antibodies against the virus, to generate data on immunity status of population and to implement containment measures accordingly.…”
Section: Introductionmentioning
confidence: 99%
“…A significant amount of the people infected with SARS-CoV-2 do not show symptoms, yet they transmit the disease to other susceptible populations (Long et al 2020;Oran and Topol 2021;Tu et al 2020). It has been reported that asymptomatic cases of COVID-19 could reach from 5% up to about 80% of all infections (Inbaraj, George, and Chandrasingh 2021;Yanes-Lane et al 2020), especially for young and healthy individuals. In slums settings like India, these estimates could reach up to more than 90% (George et al 2021;Velumani et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is imperative to identify an infected individual at the early stage of the infection and trace all possible contacts in order to break the transmission paths, and also to prevent more rapid spread of the pandemic. However, recognizing an asymptomatically (and pre-symptomatic) infected individual is practically difficult (and sometimes impossible) since they don't seek medical attention, which helps to identify their exposure to the disease (Gao et al 2021;Inbaraj, George, and Chandrasingh 2021). As a result, relevant authorities, including the WHO, did not recommend absolute reliance on the morbidity and mortality cases identified through RT-PCR since it is very likely to have potential under-reporting issues (Inbaraj, George, and Chandrasingh 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The likelihood of rapid virus dispersal throughout the crowd and subsequently (upon their return to villages and cities all over the Indian subcontinent) the country was very high. Amidst the ongoing MahaKumbh festival in April, an increase of nearly 89-fold in COVID-19 cases has been documented in Uttarakhand compared to February (the initial period of the festival) ( Upadhyay, 2021 ), with scores of transmissions that have not been picked up by clinical diagnostics ( Inbaraj et al, 2021 ). The number of confirmed positive cases that have been found among MahaKumbh returnees across the country (~0.4 million cases on May 8, 2021, a global record), clearly indicates to what immense extend congregated religious gathering has fuelled India's coronavirus outbreak and led to the spread of the pandemic into even remote villages ( Bhutta et al, 2021 ).…”
mentioning
confidence: 99%